Answer:
B
Step-by-step explanation:
Answer:
Firstly, rewrite the equation:
⅓ (18 + 27) = 81
Substitute x for the given number of it's supposed equivalent.
In this case x = 12.
⅓ (18(12) + 27) = 81
Solve using PEMDAS and simplify what is in the parenthesis first. Then, multiply.
(18 x 12) + 27 = 243
Now, solving using PEMDAS, multiply the total of what you got that was originally in the parenthesis by ⅓ .
⅓ (243) = 81
When you multiple these number they are equivalent to 81.
81 = 81
Since the equation given, when substituted x for 12, is equivalent to 81, this proves that substituting x for 12 makes this equation true.
Answer: The given logical equivalence is proved below.
Step-by-step explanation: We are given to use truth tables to show the following logical equivalence :
P ⇔ Q ≡ (∼P ∨ Q)∧(∼Q ∨ P)
We know that
two compound propositions are said to be logically equivalent if they have same corresponding truth values in the truth table.
The truth table is as follows :
P Q ∼P ∼Q P⇔ Q ∼P ∨ Q ∼Q ∨ P (∼P ∨ Q)∧(∼Q ∨ P)
T T F F T T T T
T F F T F F T F
F T T F F T F F
F F T T T T T T
Since the corresponding truth vales for P ⇔ Q and (∼P ∨ Q)∧(∼Q ∨ P) are same, so the given propositions are logically equivalent.
Thus, P ⇔ Q ≡ (∼P ∨ Q)∧(∼Q ∨ P).
Answer:
b. {(-1.5, 9.5), (1,7)}
Step-by-step explanation:
brainliest please? :)